2016
DOI: 10.1007/s11239-016-1401-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased soluble GPVI levels in cirrhosis: evidence for early in vivo platelet activation

Abstract: Cirrhosis is a consequence of prolonged liver injury and is characterised by extensive tissue fibrosis: the deposition of collagen-rich extracellular matrix. The haemostatic balance is disordered in cirrhosis and coagulation activation appears to promote fibrosis. In spite of recent studies demonstrating a role for anticoagulant therapy in preventing cirrhosis progression, there has not been a change in clinical practice, suggesting that physicians are reluctant to anticoagulate patients with cirrhosis due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Furthermore, since sGPVI is platelet-specific and the level of sGPVI depends on platelet counts, it is necessary to adjust sGPVI level by platelet counts to evaluate the actual platelet activation. 23,29 On the other hand, since endothelial cell injury plays an important role in thrombus formation, VWF and VWFpp have recently received much attention. von Willebrand factor and VWFpp are mainly synthesized by vascular endothelial cells and megakaryocytes and mediate the adhesion of platelets to sites of vascular damage by binding to specific platelet membrane glycoproteins Ib in primary thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, since sGPVI is platelet-specific and the level of sGPVI depends on platelet counts, it is necessary to adjust sGPVI level by platelet counts to evaluate the actual platelet activation. 23,29 On the other hand, since endothelial cell injury plays an important role in thrombus formation, VWF and VWFpp have recently received much attention. von Willebrand factor and VWFpp are mainly synthesized by vascular endothelial cells and megakaryocytes and mediate the adhesion of platelets to sites of vascular damage by binding to specific platelet membrane glycoproteins Ib in primary thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…22 Recently, Egan et al reported that sGPVI levels were significantly higher in patients with LC than those in healthy patients. 23 To the best of our knowledge, there have been no reports on the relationship between sGPVI levels and PVT.…”
Section: Introductionmentioning
confidence: 98%
“…(39) Moreover, data suggest in vivo platelet activation (Table 3) due to hyperactive platelets or in vivo thrombin generation (see below). (35,36,(40)(41)(42)(43)(44)(45) Low-grade endotoxemia could play a role, as bacterial lipopolysaccharides are increased in LC and correlate with in vivo platelet activation markers. (39) Differences between peripheral and portal circulation are possible, with higher platelet activation in the portal circulation.…”
Section: Thrombocytopathymentioning
confidence: 99%
“…Increased β-TG, PF-4, P-selectin, circulating CD40L (40)(41)(42)(43) No increase of these biomarkers, (35) hypothetical decreased clearance…”
Section: Soluble Biomarkersmentioning
confidence: 99%
“…The blood samples were either sent for clinical routine examinations, or were centrifuged within one hour, aliquoted in cryotubes and stored in -70 for subsequent biomarker measurements During study III analysis of plasmin-antiplasmin complex (PAP), thrombin-antithrombin complex (TAT), soluble fibrin, and soluble P-selectin was performed at the Department of Clinical Chemistry, University Hospital, Linköping. Soluble glycoprotein VI (GPVI) was analyzed by a newly described ELISA 130,131 . ACT was performed in the operating theater with Hemochron Jr, Signature, ICT, Edison, USA.…”
Section: Blood Samples Study Imentioning
confidence: 99%